Franc Kramar in njegova zbirka "Ižanskega in drugega narodnega blaga" - Kropej, Monika (Traditiones (Ljubljana), 2005)
The autor analyzes the work of composer Franc Kramar from Matena by Ig in Lower Carniola, focusing primarily on his role of a collector of folk narratives. As a youth, Kramar started to record on paper folk songs along with other material, especially folktales, anecdotes, humorous stories, invocations, folk prayers, folk belive, prophesies, riddles, and children's games. Intending to publish this material in a publication with the title Ižansko in drugo narodno blago (Oral Tradition from Ig and Other Regions), he seek advice and recommendation from lawyer and author of humorous and children's stories Fran Milčinski. Upon examining the material submitted by Kramar in 1914 Milčinski wrote a recommendation, but the onset of the First World War prevented the printing of the book.
Keywords: Kramar, Franc, 1890-1959; biografije; ethnology; etnologija; folkloristics; folkloristika; slovensko ljudsko slovstvo; slovenske ljudske pesmi; slovenske ljudske pravljice; slovensko ljudsko izročilo; zgodovinski pregledi